Further addition to the crabronid fauna of Saudi Arabia (Hymenoptera: Apoidea (Spheciformes): Crabronidae), with new genera and species records, and the description of two new species - El-Ghiet, Usama M. Abu; Gadallah, Neveen S.; Gasib, Abdulmajeed M.; Fifi, Zarrag I. A. Al-; Edmardash, Yusuf A. (Zootaxa, 2023)
The present study is based on specimens collected from the Farasan Archipelago (southwestern Saudi Arabia), and Sala Mountain (Jazan) using Malaise traps. Eleven species in six genera and two subfamilies (Bembicinae, Crabroninae) are recorded. The genera Ammatomus A. Costa (with one species), Solierella Spinola (with two species), and Nysson Latreille (with a new species) are first recorded from Saudi Arabia. Tachysphex nitidior de Beaumont, is also first record from Saudi Arabia. Two new species: Miscophus sauditus Gadallah and Edmardash, and Nysson arabicus Gadallah and Edmardash are described and illustrated. All eleven species are new to the Farasan Archipelago. Diagnostic features, previous records to species already known from Saudi Arabia, and overall distributions are given. Illustrations of the recorded species are also provided.